Should Latin America Save More to Grow Faster? - de la Torre, Augusto (World Bank, Washington, DC, 2015)
Latin America’s historically low saving rates and sub-par growth performance raise the question of whether the region should save more to grow faster. Economists generally resist acknowledging a policy-exploitable causal connection going from saving to growth because domestic saving is perceived to be fully endogenous, optimally determined, or fully substitutable by foreign saving. However, to the extent that these three assumptions do not hold, three channels can be established through which higher domestic saving—by curbing persistent current account deficits—can promote medium-term growth. The channels are first, a real interest rate channel, whereby higher saving reduces the cost of capital and enhances macro sustainability; second, a real exchange rate channel, through which higher saving leads to a more competitive real exchange rate; and third, an endogenous saving channel, whereby saving follows growth and, hence, subsequently compounds the effect of the first two channels. Econometric evidence supports all three channels and suggests that the lower-saving countries in Latin America and the Caribbean, especially those with recurrently weak balance of payments and persistent domestic demand pressures on the non-tradable sector, would benefit the most from boosting their saving rates.